Antibacterial and antibiofilm activities of eugenol from essential oil of Syzygium aromaticum (L.) Merr. & L. M. Perry (clove) leaf against periodontal pathogen Porphyromonas gingivalis. (December 2017) - Zhang, Yi; Wang, Yue; Zhu, Xiaojing; Cao, Ping; Wei, Shaomin; Lu, Yanhua
Abstract: The antibacterial effect and mechanism of eugenol from Syzygium aromaticum (L.) Merr. & L. M. Perry (clove) leaf essential oil (CLEO) against oral anaerobe Porphyromonas gingivalis were investigated. The results showed that eugenol, with content of 90.84% in CLEO, exhibited antibacterial activity against P. gingivalis at a concentration of 31.25 μM. Cell shrink and lysis caused by eugenol were observed with Scanning Electron Microscopy (SEM). The release of macromolecules and uptake of fluorescent dye indicated that the antibacterial activity was due to the ability of eugenol to permeabilize the cell membrane and destroy the integrity of plasmatic membrane irreversibly. In addition, eugenol inhibited biofilm formation and reduced preformed biofilm of P. gingivalis at different concentrations. The down-regulation of virulence factor genes related to biofilm ( fimA, hagA, hagB, rgpA, rgpB, kgp ) explained that eugenol suppressed biofilm formation at the initial stage. These findings suggest that eugenol and CLEO may be potential additives in food and personal healthcare products as a prophylactic approach to periodontitis. Highlights: Eugenol exhibited a strong antibacterial activity against planktonic P. gingivalis. Eugenol damaged the cell membrane of P. gingivalis. Eugenol suppressed biofilm formation of P. gingivalis at the initial stage. Eugenol down-regulated the expressions of virulence factor genes related to biofilm of P. gingivalis. Eugenol is a potential and effective antibacterial additive for peridontitis prevention.